Plastenke - material za izdelovanje testnih ležišč v protetiki zgornjih udov - Burgar, Matej (Rehabilitacija (Ljubljana), 2012)
Background: The socket is the most important part of a prosthesis. It is a connection between the stump and the prosthesis. It has to be comfortable, strong and has to assure transmission of forces from the body to the prosthesis. It is not simple to produce a socket which can assure those demands. During application of an upper limb prosthesis we usually produce one or more test sockets. This procedure is very important, especially during the first application of the prosthesis after amputation when the shaping of the stump is not yet finished. The procedure can increase the costs of producing a prosthesis. For this reason, we tried to find a cheaper way for produce test sockets before the application of the first prosthesis. The aim of our study was to test the technology of producing the test sockets and test prostheses from plastic bottles. We examined advantages and disadvantages of the procedure and estimated approximate costs. Methods: First, different plastic bottles were tested: different shapes, volumes and materials of bottles were shaped on plaster models. When the technology was accepted, sockets from plastic soda bottles were produced for fifteen persons after upper limb amputation. We made notes on the work process and estimated the costs in terms of time and material used. We also made notes on the testing procedure with sockets and prosthesis from plastic bottles. We compared the work process and the costs with the commonly used test sockets from thermoplastic material. We also produced and tested the usefulness of four test prosthesis. Results: The most suitable plastic bottles for making sockets were found to be those made for drinks with CO2 and preferably with a narrower opening, where the placement of the terminal advice is. The best test sockets from plastic bottles were made for the subjects following wrist disarticulation, for adults with short transradial stumps and for children. The technique saves material and time required for the production of test sockets. With this technique, we produced temporary body-powered prostheses for transradial amputees and for subjects after wrist disarticulation. We used six 1.5-litre plastic bottles. The temporary prosthesis made from plastic bottles can be used for two to three weeks in occupational therapy. Conclusion: It is possible to produce test sockets from plastic bottles for the subjects after wrist disarticulation, for adults with short transradial stumps and for children. The production of test sockets from plastic bottles reduces costs of production in terms of time and material.
Keywords: amputacija; Amputation; proteze; rehabilitacija; Rehabilitation; test sockets; testna ležišča za proteze; Upper extremity; vocational rehabilitation; zgornji ud